2013
DOI: 10.1200/jco.2012.42.7252
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Off-Label Use and Spending in 2010 Among Patent-Protected Chemotherapies in a Population-Based Cohort of Medical Oncologists

Abstract: A B S T R A C T PurposeThe prevalence of off-label anticancer drug use is not well characterized. The extent of off-label use is a policy concern because the clinical benefits of such use to patients may not outweigh costs or adverse health outcomes. MethodsPrescribing data from IntrinsiQ Intellidose data systems, a pharmacy software provider maintaining a population-based cohort database of medical oncologists, was analyzed. Use of the most commonly prescribed anticancer drugs ("chemotherapies") that were pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
104
3
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(114 citation statements)
references
References 32 publications
(9 reference statements)
2
104
3
5
Order By: Relevance
“…There are no out-ofpocket caps for beneficiaries, and coverage of oncolytics is essentially guaranteed for US Food and Drug Administrationapproved indications and many off-label uses as well. 5 The ASP plus 6% reimbursement has recently come under attack. In the 2012 budget sequester, Congress mandated that CMS cut Part B drug reimbursement by 2%.…”
Section: Introductionmentioning
confidence: 99%
“…There are no out-ofpocket caps for beneficiaries, and coverage of oncolytics is essentially guaranteed for US Food and Drug Administrationapproved indications and many off-label uses as well. 5 The ASP plus 6% reimbursement has recently come under attack. In the 2012 budget sequester, Congress mandated that CMS cut Part B drug reimbursement by 2%.…”
Section: Introductionmentioning
confidence: 99%
“…The frequence of off-label use was 30% of that half was clinically supported by the National Comprehensive Care Network (NCCN). Among agents, the rate of off-label utilization also varied considerably between trastuzumab (1%) and rituximab (67%) [12] . Another American study based on insurance administrative database found a rate of off-label use of rituximab of 25.3% during the period 2001-2007 [13] .…”
Section: Prevalence and Clinical Evidencementioning
confidence: 99%
“…A similar study has been conducted in the United States in 2010 using patient database and focusing on the off-label use of some expensive intravenous agents (including the monoclonal antibodies cetuximab, rituximab, trastuzumab, bevacizumab) [12] . The frequence of off-label use was 30% of that half was clinically supported by the National Comprehensive Care Network (NCCN).…”
Section: Prevalence and Clinical Evidencementioning
confidence: 99%
“…This is of particular interest in oncology, where patients enrolled in trials are often younger and healthier than the average cancer patient, and because there is considerable off-label treatment in settings where a large randomized trial may never be done [29]. Given that EHRs are used in routine clinical practice, issues concerning consent to data usage and patient privacy are of central concern when data are used for research.…”
Section: Ethical Issues With Emerging Research Practicesmentioning
confidence: 99%